Plastic rotation capacity of lightweight-aggregate concrete beams - Bernardo, Luís F. A.; Nepomuceno, Miguel C. S.; Pinto, Hugo A. S. (Journal of Civil Engineering and Management, 2016)
This article describes a study on the plastic behaviour of lightweight-aggregate concrete beams. The experimental results of nineteen simply supported beams previously tested by the authors were used in this study. The experimental plastic rotation capacity of the tested beams was characterized by a parameter called Plastic Trend Parameter (PTP). The main variables studied were the concrete compressive strength and the longitudinal tensile reinforcement ratio. It was found that plastic rotation capacity slightly increases as the concrete compressive strength increases. An appropriate range for the longitudinal tensile reinforcement ratio to ensure plastic rotation capacity is proposed. The results of this study were also compared with the requirements from some codes of practice. From this analysis, it was shown that ACI Code requirements give more guaranties as far as plastic rotation capacity is concerned, when compared with European codes. First published online: 28 Jan 2016